Mycoplasma hominis meningitis in an extremely preterm newborn: a case report - Najmus Sehr Ansari; Elizabeth Asztalos; Asaph Rolnitsky (BMC, 2021)
Abstract Background Mycoplasma Hominis is a micro-organism which is a part of the human genitourinary tract flora. Neonates are susceptible to acquire this pathogen either in utero or through vertical transmission. In rare cases, it may cause central nervous system infections with severe morbidity and mortality in preterm and term neonates. Case presentation We present a case of Mycoplasma Hominis meningitis in an extremely preterm neonate who presented with lethargy, tachycardia and seizures on day 7 of life. There was no history of maternal systemic or genitourinary infection during pregnancy and at the time of delivery. Empirical antibiotic therapy for neonatal meningitis was commenced after sending blood and cerebrospinal fluid cultures. Cerebrospinal fluid analysis showed pleocytosis with neutrophilic predominance, but no bacteria was identified on gram staining. Blood culture yielded no growth of any bacterial pathogen. However, growth of Mycoplasma Hominis was suspected in cerebrospinal fluid culture which was confirmed by 16S ribosomal ribonucleic acid (RNA) polymerase chain reaction analysis. Subsequently, antibiotics were changed to Moxifloxacin and Doxycycline which were given for a total duration of 6 weeks. Multiple cerebrospinal fluid cultures were performed during this treatment. No growth of any pathogen was identified on any of these cerebrospinal fluid cultures. Conclusions We report a rare case of Mycoplasma Hominis meningitis in an extremely preterm neonate which was successfully treated with a combination therapy of Moxifloxacin and Doxycycline. It is important to consider the possibility of Mycoplasma Hominis meningitis in neonates who present with clinical signs and pleocytosis in cerebrospinal fluid but negative gram staining and no growth on conventional culture media.